2013
DOI: 10.4025/cienccuidsaude.v12i3.20838
|View full text |Cite
|
Sign up to set email alerts
|

<b>Crenças em saúde de pessoas negras hipertensas sobre o estresse</b> DOI: 10.4025/cienccuidsaude.v12i3.20838

Abstract: RESUMOEste é um estudo descritivo e exploratório que objetivou descrever as crenças em saúde de pessoas negras hipertensas sobre o controle do estresse e levantar os fatores sociodemográficos envolvidos. Um instrumento específico foi utilizado para entrevistar os 106 participantes, todos adultos, negros e hipertensos. Os dados foram analisados em percentuais, frequência de casos, escores e razão de prevalência. A análise global possibilitou evidenciar que os participantes mostraram-se indecisos quanto a evitar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Todavia, estudos indicam que a Doença Arterial Coronariana apesar de acometer indivíduos de todos os grupos étnicos do mundo, sua incidência é maior entre as pessoas pretas (AL-LAGE et al 2022). A literatura destaca que este acometimento arterial pode ser resultante de uma predisposição genética em pretos, além de ser uma população mais exposta em termos sociais aos fatores de risco inerentes à doença arterial (MALTA et al 2022;PIRES;MUSSI, 2013;;LESSA et al 2006).…”
Section: Discussionunclassified
“…Todavia, estudos indicam que a Doença Arterial Coronariana apesar de acometer indivíduos de todos os grupos étnicos do mundo, sua incidência é maior entre as pessoas pretas (AL-LAGE et al 2022). A literatura destaca que este acometimento arterial pode ser resultante de uma predisposição genética em pretos, além de ser uma população mais exposta em termos sociais aos fatores de risco inerentes à doença arterial (MALTA et al 2022;PIRES;MUSSI, 2013;;LESSA et al 2006).…”
Section: Discussionunclassified
“…It was also observed that they did not mention the contents of the leisure activities, suggesting the low criticality and understanding of the physical, practical artistic, intellectual, social, virtual, and tourist interests that must be considered in leisure practices (1,11,19) . The theoretical framework of leisure does not merely apply to interventions in the time available to the population, but also to interventions that target personal development (4,11) and help improve the quality of life in a comprehensive manner that is not restricted to the absence of disease, as highlighted by the participants of this study.…”
Section: Investigative Momentmentioning
confidence: 99%
“…Nothing would be more fitting than to consider leisure as an instrument of education since individuals who participate in leisure activities are also developing individually and socially (9)(10)(11) . In this regard, technological developments have reconfigured leisure practices and educational strategies, and virtual tools have been used to guide the learning process in an enjoyable and timely manner (12)(13) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations